2006
DOI: 10.1063/1.2357641
|View full text |Cite
|
Sign up to set email alerts
|

A compact equivalent circuit for the dark current-voltage characteristics of nonideal solar cells

Abstract: This paper presents a compact electrical equivalent circuit which describes the dark current-voltage characteristics of nonideal p-n junction solar cells in a wide range of temperatures. The model clearly separates the voltage drop in the junction and bulk regions. It is based on the combination of two exponential mechanisms, shunt and series resistances and space-charge limited current. In order to increase the accuracy of the parameter extraction process, both ln(I-V) and its derivative plots are fitted simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…1 shows the variation of model with the measured data for 5 different solar cells. 1,[14][15][16][17] It is observed that the model characteristics like fill factors, maximum power points for all these cells match closely with the measured data. Our model is validated for some of the standard cells and listed in Table I.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…1 shows the variation of model with the measured data for 5 different solar cells. 1,[14][15][16][17] It is observed that the model characteristics like fill factors, maximum power points for all these cells match closely with the measured data. Our model is validated for some of the standard cells and listed in Table I.…”
Section: Resultssupporting
confidence: 83%
“…Usually, polynomial equations are preferred to represent the practical J-V characteristics over equivalent circuit representation that involves iterative calculation in parameter extraction. [1][2][3][4][5][6][7] For an illuminated solar cell having parasitic series and shunt resistances, the simplest of the current density-voltage equation called the Single Exponential Model (SEM), 8 which is given as…”
Section: Introductionmentioning
confidence: 99%
“…8,9,13,18,19 Some equivalent circuits incorporating a parasitic weak diode have also been proposed to account for these nonlinear shunts. [19][20][21] However, these macroscopic, circuit level models cannot account for the microscopic nature of shunt paths. The physical origin of shunt conduction paths have also been explored in the literature.…”
Section: ͑1͒mentioning
confidence: 99%
“…4 shows the equivalent circuit of the solar cells operated at the forward bias voltage, where R s and R sh are the series resistance and the shunt resistance, respectively. The dark current density at the low current level was mainly influenced by the shunt resistance associated with the carrier recombination loss (Pallares et al, 2006;Tseng and Lee, 2012). It could be found that the dark current density at the low current level of the RE-GOS-cell revealed almost identical with that of the SE-GOS-cell.…”
Section: Resultsmentioning
confidence: 72%